Proposing conceptual framework for reducing earning management using ownership structure mechanism: Jordanian companies perspective - Alzoubi, Ebraheem Saleem Salem; Selamat, Mohamad Hisyam (Global Strategic Management Incorporated, USA, 2012)
This paper evaluates as well as synthesizes the empirical studies results of the relationship between one mechanism of corporate governance and financial reporting quality (FRQ).The authors study one oversight mechanism that is ownership structure.For the mechanism, the authors recapitulate the links between variable monitoring effectiveness contribution and monitoring outcomes of FRQ namely earnings management (EM).The system arrangement affords synthesizing the empirical findings allegation, highlighting the mechanism of corporate governance role in improving FRQ. This probable synthesis inform regulators, board of directors and accountants who are apprehensive with enhancing the public and private corporations oversight in addition to decreasing managers and others the opportunities to engage in EM. The ownership structure components are insider managers, institutional investors, and block-holders that can improve the FRQ.